2007
DOI: 10.1088/0022-3727/40/3/014
|View full text |Cite
|
Sign up to set email alerts
|

The role of backscattered energetic atoms in film growth in reactive magnetron sputtering of chromium nitride

Abstract: In this work the impact of backscattered energetic atoms on film growth in reactive sputtering of CrN x (x 1) is manifested. We use film and plasma characterization techniques, as well as simulations in order to study the dynamics of the target-discharge-film interactions. The results show that the primary bombarding species of the growing film are N + 2 plasma ions, which are neutralized and backscattered by the target in the form of atomic N. It is shown that the backscattered N atoms have energies which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We attribute the increased compressive stress upon introduction of N 2 in the processing gas to N 2 + -ions that are implanted in the growing film, occupy interstitial sites, and cause compressive stress; while the majority of implanted Ar + ions will diffuse to the surface, causing less pronounced stress. In addition, backscattered N-atoms have a higher energy than backscattered Ar and, in turn, can cause larger layer densification and compressive stress [49,50]. The reduction in the compressive stress for y N 0.44 is attributed to the increasing fraction of the amorphous matrix phase, as evidenced by the larger C-C and C-N bond fraction measured by XPS, which may provide pathways for stress relaxation through diffusion of interstitial C and N from the Nb-carbonitride phase to the amorphous matrix phase as well as plastic shear deformation within the amorphous matrix.…”
Section: Residual Stress and Hardnessmentioning
confidence: 99%
“…We attribute the increased compressive stress upon introduction of N 2 in the processing gas to N 2 + -ions that are implanted in the growing film, occupy interstitial sites, and cause compressive stress; while the majority of implanted Ar + ions will diffuse to the surface, causing less pronounced stress. In addition, backscattered N-atoms have a higher energy than backscattered Ar and, in turn, can cause larger layer densification and compressive stress [49,50]. The reduction in the compressive stress for y N 0.44 is attributed to the increasing fraction of the amorphous matrix phase, as evidenced by the larger C-C and C-N bond fraction measured by XPS, which may provide pathways for stress relaxation through diffusion of interstitial C and N from the Nb-carbonitride phase to the amorphous matrix phase as well as plastic shear deformation within the amorphous matrix.…”
Section: Residual Stress and Hardnessmentioning
confidence: 99%
“…It has been shown that film properties, such as high compressive stresses and high roughness can be explained by the energy of the incident species on the surface of the growing film [30,31]. It is shown that when the energy of the incident species on the film surface is low, their energy transfers to the surface of the growing film and affects the surface roughness [5,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that when the energy of the incident species on the film surface is low, their energy transfers to the surface of the growing film and affects the surface roughness [5,31,32]. On the other hand, the species are supplanted into the film when their energy increases, which, in turn, forms higher internal stresses [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…9 To find out the nitrogen pressure required during the deposition, modelling of the reactive sputtering process could be employed, for instance as developed by S. Berg et al 11 However, without precise values of the La and LaN sputtering yields (reactive deposition), the sticking coefficient of nitrogen to lanthanum, without taking into account nitrogen ion implantation into the target, etc., accurate calculations seem to be impossible. Moreover, in the plasma N • , N + , and N + 2 are produced via various electron-impact reactions, 12 and positively charged species impinge the La target, neutralize (with certain probability) and reflect back, in the direction of the growing La layer, 13 performing additional nitridation of deposited La. Modern advanced models of reactive deposition, for instance 14 require extraction of certain parameters by fitting the experimental data, 15 which is time consuming.…”
Section: Synthesis Of Fully-passivated Lanmentioning
confidence: 99%